2021
DOI: 10.7759/cureus.15572
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Ferritin in Determining Sexual Underdevelopment in Beta-Thalassemia Major Patients: A Cross-Sectional Analysis From Pakistan

Abstract: BackgroundBeta-thalassemia major, a genetic disorder, delineates a vast spectrum of hematological and endocrinological complications. Elevated serum ferritin levels in beta-thalassemia patients represent various transfusion-related complications including infection, hemochromatosis, and severe iron overload that might lead to endocrinopathies such as hypogonadism leading to sexual underdevelopment. Our study, thus, aims to explore the role of ferritin in determining sexual underdevelopment in such patients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Patients in the pubescent (stage 3) or post-pubescent (stages 4 and 5) stages, on the other hand, were deemed sexually developed. 19 The gonadal function of the patient was evaluated by history, physical examination and laboratory tests, including the serum luteinizing hormone (LH), serum follicle-stimulating hormone (FSH), serum testosterone for males and serum estradiol for females. The serum ferritin level was also measured to assess the iron overload status of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the pubescent (stage 3) or post-pubescent (stages 4 and 5) stages, on the other hand, were deemed sexually developed. 19 The gonadal function of the patient was evaluated by history, physical examination and laboratory tests, including the serum luteinizing hormone (LH), serum follicle-stimulating hormone (FSH), serum testosterone for males and serum estradiol for females. The serum ferritin level was also measured to assess the iron overload status of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…TED-related hypogonadism is due to IO, general health status, BTH complications, and potential side effects of different regimes. It manifests during puberty or adult life, either as primary or secondary amenorrhea in females [ 51 , 52 ]. Its prevalence varies among studies, related especially to whether or not the pubertal status is taken into consideration.…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
“…According to one study, the prevalence is 23.6% among patients at puberty age, and ferritin negatively correlates with pituitary volume [ 27 ]. Some suggested that puberty failure might be predicted by serum ferritin [ 22 , 52 ]. A transversal study from a single tertiary centre included 58 patients (33/58 males) with transfusion-dependent TH (aged between 17 and 19 y) and 72.4% of subjects experienced either normal puberty or delayed onset with spontaneous progression, but 26.7% of them experienced arrested puberty requiring hormonal intervention.…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
“…Transfusion-dependent beta-thalassemia (TDT) is a common hereditary disease caused by mutations in the gene encoding β-chains of hemoglobin (Hb) which leads to the reduced or absent synthesis of the β-globin chain in Hb tetramers. [1] These patients require continuous blood transfusions or bone marrow transplantation for their survival [2]. According to the World Health Organization (WHO), about 25,500 neonates globally are born with TDT each year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, hydroxyurea (HU) and thalidomide have emerged as notable HbF inducers, leading to a significant increase in HbF concentrations in TDT patients [1,15]. Studies have also shown an alarmingly high mortality rate in beta-thalassemic patients with increased ferritin levels [2]. ICT can decrease the morbidity associated with iron toxicity.…”
Section: Introductionmentioning
confidence: 99%